Особенности лингвокультурологии как филологической дисциплины - TOPBAŞOĞLU ERAY, Keziban (RumeliDE Dil ve Edebiyat Araştırmaları Dergisi :/RumeliDe Dil ve Edebiyat Araştırmaları Dergisi, 2022)
Cтатья посвящена рассмотрению наиболее общих представлений о лингвокультурологии как об интегративной гуманитарной дисциплине, ее базовых единицах и категориях. Отмечено, что на сегодняшний день в научном мире распространено несколько дефиниций понятия «лингвокультурология». В статье придерживаемся определения В.В. Красных, квалифицирующей лингвокультурологию как науку, которая изучает, как отражается культура в языке и речи. Лингвокультурология напрямую связана с национальной картиной мира, языковым сознанием и особенностями менталитета. Обращено внимание на историю возникновения лингвокультурологии, ее теоретическую основу (объект, предмет, цель, задачи, принципы), выделено этапы развития этой молодой лингвистической дисциплины. Лингвокультурология опирается на три главных принципа (антропоцентризм, когнитивизм, лингвокультурологизм) и рассматривается как один из «продуктов» становления антропоцентрической парадигмы, которая сформировалась в ХХ веке и сегодня является основной в лингвистике. Указано место лингвокультурологии среди других гуманитарных дисциплин: больше всего она связана с лингвоисторическими дисциплинами, такими как культурология, этнолингвистика, этнопсихолингвистика, лингвострановедение, а также лингвистикой (лексикологией, фразеологией, семантикой и т.п.). Лингвокультурология как наука и учебная дисциплина прошла достаточно долгий и сложный путь развития, но сегодня уже нет сомнений в том, что она представляет отдельную область знаний с собственным объектом, предметом исследования и методологией. Эта наука пока еще находится в стадии становления, но на сегодняшний день уже выделено несколько основных принципов и базовых положений, определяющих направление научных исследований в этой области знаний. В статье также проанализированы такие основные понятия и категории лингвокультурологии как лингвокультурема, логоэпистема, лингвокультурный концепт, стереотип, символ, мифологема, архетип и др. Базовым понятием лингвокультурологии является лингвокультурный концепт. Отдельное внимание уделено понятиям языковой личности, языковой компетенции, культурной компетенции, ментальности, менталитету. Отмечено различия языковой и когнитивной (концептуальной) картин мира. The article is devoted to the consideration of the most general ideas about linguoculturology as an integrative humanitarian discipline and its basic concepts and categories. It is noted that today in the scientific world there are several definitions of the concept of "linguoculturology". In the article we adhere to the definition of V.V. Krasnykh, which qualifies linguoculturology as a science that studies how culture is reflected in language and speech. Linguoculturology is directly related to the national picture of the world, linguistic consciousness and mentality. Attention is drawn to the history of the emergence of linguoculturology and its theoretical basis (object, subject, goal, tasks, principles); and the stages of development of this young linguistic discipline are highlighted. Linguoculturology is based on three main principles (anthropocentrism, cognitivism, linguoculturalism) and is considered to be one of the “products” of the anthropocentric paradigm, which was formed in the 20th century and today is dominant in linguistics. The place of linguoculturology among other humanitarian disciplines is indicated: in particular, it is connected with linguo-historical disciplines, such as cultural studies, ethnolinguistics, ethnopsycholinguistics, and linguistic and regional studies, as well as linguistics (lexicology, phraseology, semantics, etc.). Linguoculturology as a science and academic discipline has followed a long and difficult path of development, but today there is no doubt that it represents a separate field of knowledge with its own objective, subject of research and methodology. This science is still in its infancy, several basic principles and basic provisions have already been identified that determine the direction of scientific research in this field of knowledge. The article also analyzes such basic concepts and categories of linguoculturology as linguoculturema, logoepistema, linguocultural concept, stereotype, symbol, mythologeme, archetype, etc. The basic concept of linguoculturology is the linguocultural concept. Special attention is paid to the concepts of linguistic personality, linguistic competence, cultural competence, and mentality. Differences in linguistic and cognitive (conceptual) pictures of the world are noted. Makale, bütünleştirici bir insani disiplin olarak kültürdilbilime ve onun temel kavram ve kategorilerine yönelik en genel fikirlerin değerlendirilmesine ayrılmıştır. Bugün bilim dünyasında "kültürdilbilim" kavramının çeşitli tanımlarının olduğu belirtilmektedir. Bu makalede, kültürdilbilimi, kültürün dile ve konuşmaya nasıl yansıdığını inceleyen bir bilim olarak nitelendiren V. V. Krasnıh’ın tanımları esas alınacaktır. Kültürdilbilim, dil dünya görüşü, dilsel bilinç ve zihniyet ile doğrudan ilişkilidir. Çalışmada kültürdilbilimin ortaya çıkış tarihine ve teorik temeline (nesne, konu, amaç, görev ve ilkeler) dikkat çekilmekte ve bu genç dil disiplininin gelişim aşamalarının altı çizilmektedir. Kültürdilbilim üç ana ilkeye (antroposentrizm, bilişselcilik, lingvokulturalizm) dayanır ve 20. yüzyılda ortaya çıkan ve günümüzde dilbilimde egemen olan antroposentrik paradigmanın “ürünlerinden” biri olarak kabul edilir. Dilbilimin diğer insani disiplinler arasındaki yerine işaret edilmektedir: daha çok kültürel çalışmalar, etnodilbilim, etnopsikodilbilim ve dilbilimsel ve bölgesel çalışmalar gibi dilbilimsel-tarihsel disiplinlerin yanı sıra dilbilim (sözlükbilim, deyimbilim, anlambilim, vb.) ile de bağlantılıdır. Bir bilim ve akademik disiplin olarak kültürdilbilim, uzun ve zorlu bir gelişim yolu izlemiştir, ancak bugün, şüphesiz, kendi amacı, araştırma konusu ve metodolojisi ile ayrı bir bilim alanını temsil etmektedir. Henüz emekleme aşamasında olsa da bu alandaki bilimsel araştırmaların yönünü belirleyen birkaç temel ilke ve hüküm hali hazırda belirlenmiştir. Makale ayrıca lingvokulturema, logoepistema, kültürdilbilimsel konsept, stereotip, sembol, mitoloji, arketip, vb. gibi kültürdilbilimin temel kavram ve kategorilerini de analiz etmektedir. Kültürdilbilimin temel kavramı kültürdilbilimsel konseptir. Dilsel kişilik, dilsel yeterlilik, kültürel yeterlilik ve zihniyet kavramlarına özellikle dikkat çekilmekte, dil dünya görüşü ve bilişsel farklılıklar odağa alınmaktadır.